1992
DOI: 10.1093/bja/68.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia for Labour and Delivery Using Incremental Diamorphine and Bupivacaine via a 32–gauge Intrathecal Catheter

Abstract: Twenty mothers who had requested regional analgesia during labour had a 32-gauge catheter inserted into the lumbar subarachnoid space. The mean time to place the catheters was 116 s (range 55-270 s) and there were no technical difficulties. Incremental diamorphine was given, up to a maximum initial dose of 0.5 mg. Analgesia was excellent in 11 mothers, good in seven and unsatisfactory in two. The duration of initial analgesia from diamorphine was 101 min (range 30-170 min). Eight mothers were able to move abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

1994
1994
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 12 publications
2
4
0
2
Order By: Relevance
“…There was no evidence of neonatal depression in the present study and similar findings have been reported previously using intrathecal diamorphine [19, 20]. This is probably due to the fact that relatively smaller doses of the drug are given by the intrathecal route compared with systemic routes of administration, thereby reducing the dose available for transfer to the fetus.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There was no evidence of neonatal depression in the present study and similar findings have been reported previously using intrathecal diamorphine [19, 20]. This is probably due to the fact that relatively smaller doses of the drug are given by the intrathecal route compared with systemic routes of administration, thereby reducing the dose available for transfer to the fetus.…”
Section: Discussionsupporting
confidence: 90%
“…Although occasional cases have been reported, respiratory depression following intrathecal diamorphine in nonobstetric cases appears to be rare even with higher doses [3, 4, 17, 18]. This appears to be true in obstetrics also [19, 20] and was confirmed in the present study. S p O 2 values below 95% were frequently observed in all groups following surgery in the present study although the differences between the groups were not significant.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Das "Titrieren" der Höhe des Anästhesieniveaus mit geringen Einzeldosen des Lokalanästhetikums ermöglicht die weitgehende Vermeidung hypotensiver Zustände: Mehrere Autoren betonen das völlige Fehlen dieser Komplikation bei Anwendung der CSA in der Geburtshilfe in größeren Kollektiven [13,16,19]. Die exzellente kardiovaskuläre Stabilität bei Anwendung der CSA wurde erst kürzlich erneut demonstriert [12].…”
Section: Regionalanästhesietechniken Zur Sectio Caesareaunclassified
“…Diese werden im Zusammenhang mit der CSA extrem selten berichtet, in Veröffentlichungen über die Anwendung der Methode in der Geburtshilfe ist diese Komplikation bisher nicht aufgetreten -strengste Beachtung der Hygiene vorausgesetzt [16].…”
Section: Infektiöse Problemeunclassified